Stage Presentation of Allegorical Characters in J. Skelton’s Play Magnyfycence - Lilova, Olena (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
The article deals with the peculiarities of constructing allegorical characters in John Skelton’s play Magnyfycence (c.1519-1520). Though the allegories of the Vices in this interlude are based on an abstract idea, they are endowed with individual features of real prototypes – certain gentlemen at the court of Henry VIII – rather than with typical traits of generalized allegorical images. The English playwright’s treatment of allegories obviously proceeds from the general idea of the play. It is emphasized that the essence of the early Tudor allegorical plays can only be rediscovered through their theatrical performance.